The History of the Greek-Catholic Church as Reflected in the Post 1989 Romanian Historiography. Some Considerations - CÂRJA, Cecilia; CÂRJA, Ion (Studia Universitatis Babeș-Bolyai Historia, 2016)
The History of the Greek-Catholic Church as Reflected in the Post 1989 Romanian Historiography. Some Considerations. The study aims to present several considerations concerning a scientific research topic which was almost non-existent prior to 1989: the history of Romanian Greek-Catholic Church. The liberalisation of the historical writing in post-communist Romania has created a favourable climate for restarting the research concerning the history of the Church and of religious life. It is in this context that the Romanian United Church became once more an important subject in the Romanian historiography. The research of the history of the Greek-Catholic Church meant , for that period, going to primary sources (archives in and outside the country), as well as identifying main research topics such as: the Union of the Transylvanian Romanians with the Church of Rome, personalities and institutions, relations between the Greek-Catholic Church with the Holly See and with the Latin Catholic Church from Austria-Hungary in the second half of the 19th century and the beginning of the 20th century, the outlawry of this Church in 1948, the period of the communist persecution etc. When surveying the topic, we are dealing with three ways of connecting with the history of the Romanian Greek-Catholic Church: academic history, a result of studies and research conducted by specialists, the official, encomiastic history automatically assumed by the United elites and clergy and a disputed history generated by a difficult dialogue and the tensed relations with the Orthodox Church following the post-communist transition. Rezumat: Istoria Bisericii greco-catolice în preocupările istoriografiei româneşti după 1989. Câteva consideraţii. Studiul îşi propune să prezinte câteva consideraţii pe marginea unui sector al cercetării ştiinţifice aproapte inexistent înainte de 1989, istoria Bisericii Greco-Catolice româneşti. Liberalizarea scrisului istoric în România post-comunistă a creat un climat favorabil pentru relansarea cercetărilor de istoria bisericii şi a vieţii religioase şi în acest context Biserica Română Unită a revenit ca o temă importantă pe agenda istoriografiei româneşti. Cercetarea istoriei Bisericii Greco-Catolice a presupus, în această perioadă, apelul la izvoare primare (fonduri de arhivă din ţară şi străinătate), precum şi identificarea unor priorităţi tematice, cum ar fi: Unirea românilor din Transilvania cu Biserica Romei, personalităţi şi instituţii, relaţiile Bisericii Greco-Catolice cu Sfântul Scaun şi cu Biserica catolică de rit latin din Austro-Ungaria în a doua jumătate a secolului al XIX-lea şi la începutul secolului XX, interzicerea acestei Biserici în 1948, anii prigoanei comuniste etc. La o privire de ansamblu asupra subiectului, se poate spune că avem de-a face cu trei tipuri de raportare la istoria Bisericii Greco-Catolice române: istoria academică, rezultat al studiilor şi cercetărilor făcute de specialişti, istoria oficială, encomiastică, autoasumată de elite şi de mediile clericale unite, o istorie polemică generată de un dialog dificil şi de relaţiile tensionate cu Biserica Ortodoxă, în anii tranziţiei post-comuniste. Cuvinte-cheie: istoriografie, Biserica Greco-Catolică, identitate, confesiune, tranziţie